Validity of Star Excursion Balance Test as Dynamic Balance Test In Subjects with Non-Operative Anterior Cruciate Ligament Injury - Yudith Dian Prawitri1, Imam Subadi1, Bayu Santoso1* (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: The anterior cruciate ligament (ACL) injury is the most common knee injury that might occur during exercise. An ACL causes a balance disorder that can be considered as a risk factor for recurring injury. Identification of balance disturbances in subjects with ACL injury should be conducted to minimize the risk of re-injury. Objectives: this study aims to determine the validity of star excursion balance test with biodex balance system SD as a gold standard Method: This study is a diagnostic test with cross-sectional study approach. The number of research sample was 20 respondents selected as control group, five people with ACL injury as the case group. All subjects were examined with the biodex balance system SD (Overall Stability Index) and star excursion balance test (% MAXD). Results: The result of the correlation analysis between the overall stability index and %MAXD was not significant with r = -0.316; p = 0.175. Hence, the cut-off point could not be determined due to the insignificant correlation, thus the sensitivity, specificity, positive predictive value, and negative predictive value of the star excursion balance test could not be determined. Conclusion: Star excursion balance test was invalid as a dynamic balance test if the Biodex Balance Test SD was used as a gold standard.